Highly efficient particle swarm optimisation for energy efficiency in wireless sensor network using energy capping and predictive energy allocation. (12th July 2021) - Reddy, Vandana; Gayathri, P.
WSN has changed the way of life for humans in the due course of technological evolution. The change has led to many improvisations and sophistication in the day-to-day usable devices. These devices help the human in daily routines and now they have been an integral part. More precisely when we consider any smart environment, we use many of the devices that are essential rather than necessities. Some of these devices could be fire sensors, smoke sensors, water level controllers, CCTV and so on. These devices are energy critical and need power source. Thus the swarm optimisation techniques are required to help find an efficient approach for energy optimisation problem in WSN. Hence, it is critical for us to devise an energy conservation mechanism using highly accurate particle swarm optimisation (PSO) in these sensors and devise an algorithm energy capping and predictive energy allocation (EC-PEA).